Software Synthesis for Hard Real-Time Embedded Systems with Energy Constraints - Tavares, Eduardo; Silva, Bruno; Maciel, Paulo; Dallegrave, Pedro (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2008)
Over the last years, the issue of reducing energy consumption in hard real-time embedded systems has received considerable attention from the scientific community, since responsiveness and low energy consumption are often conflicting requirements. In this context, several techniques have been proposed, mostly, adopting DVS (dynamic voltage scaling) for reducing energy consumption in conjunction with runtime scheduling policies for dealing with stringent timing constraints. Nevertheless, those approaches generally disregard inter-task relations and runtime overheads (e.g. voltage switching) as well as adopt specialized operating systems. This paper presents a software synthesis method for hard real-time systems with energy constraints, taking into account DVS, inter-task relations and runtime overheads. The proposed method adopts a formal model based on time Petri nets in order to provide a basis for precise pre-runtime schedule generation.